Hatha Yoga Sebagai Terapi Alternatif Pada Nyeri Kepala - Ni Wayan Yusi Armini; Diah Nirmala Dewi (Jurnal Yoga dan Kesehatan, 2021)
Headaches often suddenly attack and this causes disruption to the various activities that are being carried out by ours. Headaches are pain in the head that can occur gradually or appear instantly almost unexpectedly. Headaches that appear can be felt light, heavy, and the area can be felt in the entire head or only in certain areas. There are many ways to deal with headaches, such as get some medication or get some massage therapy at certain points area, depending kind of headaches. However, the use of pain medication usually only has a short-term impact, so that at any time this headache reappears. Yoga therapy is an alternative in dealing with this headache. Yoga is indeed known as an alternative healing for certain diseases, one of them is headache. Although there is no exact and in-depth research on this issue, but some yoga movements are said to be able to deal with headaches, especially for those who often experience this headache attack at the wrong time, for example.